Transformation of the psyche : the symbolic alchemy of the Splendor solis - Henderson, Joseph L. (Joseph Lewis), 1903-2007 (Brunner-Routledge, 2003)
Transformation of the Psyche is a truly unique book that will be of immense value and interest to analysts and psychotherapists, as well as scholars of mediaeval and renaissance intellectual history and students of spiritual disciplines.